PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IPA SMAN 1 V KOTO KAMPUNG DALAM - Anggia Rahma Milenia (Jurnal Edukasi dan Penelitian Matematika, 2022)
Mathematical concept understanding constitute a basis goal that should be achieved when learning subject mathematics, because in the learning process definitely requires understanding and meaning of the material being studied. However, based on the data from the daily assessment on linier program material is obtained by the fact that the mathematical understanding of the concepts of students is still low. The action that can be done to cope with this problem is to implement the cooperative model type Student Teams Achievement Divisions (STAD). Research type that chosen is quasi experimental. The population in this research are all students of class XI IPA SMAN 1 V Koto Kampung Dalam for academic year 2022/2023 which consists of four classes. Based on the quiz research, the mathematical concept understanding is experiencing development by implementation of type STAD. Besides that, the results of the hypothesis test, it obtained that P - Value = 0.016 < 0,05, which means to reject . So that the conclusion is obtained that the mathematical concept understanding students of experimental class is better than the mathematical concept understanding concept students of control class.   Keywords– understandings mathematicals concepts, Student Teams Achievement Divisions, Non Equivalent Post Test Only Group Design